PENGARUH DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK) DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA MODAL PEMERINTAH KOTA PALEMBANG - A. Surakhman; Abid Djazuli; Choiriyah Choiriyah (KOLEGIAL, 2020)
This study aims to study and analyze General Allocation Funds, Special Allocation Funds and Regional Original Revenues on Capital Expenditures in the City of Palembang in the past 10 years. The research design used in this study is an associative method. The analytical model used is quantitative. The variables used are DAU, DAK and PAD as independent variables and Capital Expenditures as independent variables. The sample used is the Palembang City ABPD data for 10 years from 2008 to 2017. The analytical tool used is the Classical Assumption Model, Multiple Regression Analysis, Determination Coefficient, F Test and t Test. Based on the results of the study it was found that (1) DAU shows a positive and significant effect on Capital Expenditures; (2) DAK is positive and significant to Capital Expenditures; (3) PAD plays a positive and significant role on Capital Expenditures, both partially and jointly.